If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -2)(4x) = 40 Reorder the terms: (-2 + 5x)(4x) = 40 Remove parenthesis around (4x) (-2 + 5x) * 4x = 40 Reorder the terms for easier multiplication: 4x(-2 + 5x) = 40 (-2 * 4x + 5x * 4x) = 40 (-8x + 20x2) = 40 Solving -8x + 20x2 = 40 Solving for variable 'x'. Reorder the terms: -40 + -8x + 20x2 = 40 + -40 Combine like terms: 40 + -40 = 0 -40 + -8x + 20x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-10 + -2x + 5x2) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-10 + -2x + 5x2)' equal to zero and attempt to solve: Simplifying -10 + -2x + 5x2 = 0 Solving -10 + -2x + 5x2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. -2 + -0.4x + x2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + -0.4x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + -0.4x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -0.4x + x2 = 0 + 2 -0.4x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 -0.4x + x2 = 2 The x term is -0.4x. Take half its coefficient (-0.2). Square it (0.04) and add it to both sides. Add '0.04' to each side of the equation. -0.4x + 0.04 + x2 = 2 + 0.04 Reorder the terms: 0.04 + -0.4x + x2 = 2 + 0.04 Combine like terms: 2 + 0.04 = 2.04 0.04 + -0.4x + x2 = 2.04 Factor a perfect square on the left side: (x + -0.2)(x + -0.2) = 2.04 Calculate the square root of the right side: 1.428285686 Break this problem into two subproblems by setting (x + -0.2) equal to 1.428285686 and -1.428285686.Subproblem 1
x + -0.2 = 1.428285686 Simplifying x + -0.2 = 1.428285686 Reorder the terms: -0.2 + x = 1.428285686 Solving -0.2 + x = 1.428285686 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2' to each side of the equation. -0.2 + 0.2 + x = 1.428285686 + 0.2 Combine like terms: -0.2 + 0.2 = 0.0 0.0 + x = 1.428285686 + 0.2 x = 1.428285686 + 0.2 Combine like terms: 1.428285686 + 0.2 = 1.628285686 x = 1.628285686 Simplifying x = 1.628285686Subproblem 2
x + -0.2 = -1.428285686 Simplifying x + -0.2 = -1.428285686 Reorder the terms: -0.2 + x = -1.428285686 Solving -0.2 + x = -1.428285686 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2' to each side of the equation. -0.2 + 0.2 + x = -1.428285686 + 0.2 Combine like terms: -0.2 + 0.2 = 0.0 0.0 + x = -1.428285686 + 0.2 x = -1.428285686 + 0.2 Combine like terms: -1.428285686 + 0.2 = -1.228285686 x = -1.228285686 Simplifying x = -1.228285686Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.628285686, -1.228285686}Solution
x = {1.628285686, -1.228285686}
| -3(x-8)=-18 | | 8x+3=45 | | 2*4/1=4 | | 9z-6+7=16z-6 | | 2*2/1 | | -8(3p-6)=192 | | 4-3a/4 | | y+8=-2(x+0) | | 28=2(x+4) | | -10=-4x-4 | | 5a-20=180 | | 4x-2/3=70/3 | | -2x+2z+3y= | | ln(x)=5.4+ln(6.5) | | 3x+6x-4x= | | f(x)=x^2+18x+60 | | -4x-18=-34 | | =12a^2b^6 | | 10x-8=-28 | | 3a+8=180 | | 4x*18+2x*6=248 | | -(4r-7)=2-5r | | 13-2+2x=x+3 | | 1.25d+3.25=1+2.25d | | x(3.5)=2.5 | | -5(-9-6)=15 | | 2.3=1/2y | | x^2+6x=573 | | -4x-18=-30 | | x^2+6x=5743 | | 6x-2(3x-5)=154 | | -66y-45x+10(7-123x)=1520 |